Producción y detección de quarks top en atlas (lhc) (2004)
After the top quark discovery at Fermilab, the top quark physics has move on from the search to the study state. The NLO predictions for σt t- = 833 pb at LHC imply a production of 8 millions top quark pairs per year at low luminosity. Using Monte Carlo methods and programs like Pythia, ROOT, ALTFAST and Geant4, a simulation of the events in pp collisions is done with an energy of the center of mass of de s1/2 = 14, which is relevant for LHC. The process pp - and gt; t t-  is studied and the subprocesses subprocesos t t- - and gt; Wb - and gt; (lυ)(jj)b, t t- - and gt; Wb - and gt; (jj)(jj)bb and t t- - and gt; Wb - and gt; (lυ) (lυ)bb too. Also the element Vtb of the CKM matrix is gotten and the top quark mass is obtained from the semileptonic channel. The framework used is the standard model of elementary particles.